EXPERIMENTAL STUDY OF THE RESEARCH PROBLEM: METHODOLOGICAL APPROACHES AND EMPIRICAL VALIDATION IN CONTEMPORARY ACADEMIC INQUIRY (SCIENCE TIME JOURNAL, 2026)
This paper analyses how experimental approaches can be used to solve complex research issues in the modern academic enquiry. Experimental design has gained prominence in the context of growing needs of evidence-based decision-making, as a method of validating theoretical assumptions and testing cause-effect relationships. The paper will discuss the role of experimental methods in identifying, analyzing, and solving research issues, focusing on their methodological rigor and empirical reliability. The study is based on theoretical analysis and empirical investigation, relying on the frameworks on experimental research.